Reserve price formation in online auctions - Florian Englmaier; Arno Schmöller (Center for Economic Studies and ifo Institute (CESifo), 2008)
We use a unique hand collected data set of 6 258 auctions from the online football manager game Hattrick to study micro-patterns of reserve price formation. We find that chosen reserve prices exhibit both, very sophisticated and irrational behavior by the sellers. Reserve prices pick up the birthday effect in sales prices, documented in Englmaier and Schmöller (2008) and are adjusted remarkably nuanced to the resulting sales price pattern. Moreover, reserve prices are too clustered (around multiples of 50 000) as to be consistent with fully rational behavior. Furthermore, we find evidence for entitlement effects and the sunk cost fallacy as there is a huge positive effect on the reserve price when the player has been acquired previously.
Keywords: D12; D44; 330; Auctions; reserve price; bounded rationality; heuristics; entitlement effect; Auktionstheorie; Internet; Preis; Bewertung; Beschränkte Rationalität; Test